High-proportion breast milk feeding is associated with a reduction in the incidence of IVH in very preterm infants - Zheng, Zhi; Shen, Wei; Tang, Li-Xia; Zhang, Rong; Cheng, Rui; Wang, San-Nan; Chen, Dong-Mei; Chen, Chao; Lin, Xin-Zhu (Frontiers in Neurology, 2023)
Objective: To investigate the protective effect of high-proportion breast milk feeding (>50%) on intraventricular hemorrhage (IVH) in very preterm infants (VPIs). Methods: This was a retrospective secondary analysis of a prospective multi-center study. The 604 VPIs from six hospitals were divided into two groups according to whether IVH occurred. High-proportion breast milk feeding was defined as breast milk accounting for 51%–100% of the total feeding amount both within 7 days and throughout the hospitalization. To explore the relationship between high-proportion breast milk feeding and IVH grading, the general information, perinatal factors, growth, nutritional status during hospitalization, and related complications of VPIs were compared between the two groups. Results: High-proportion breast milk feeding was reported in 63.41% of the VPIs. IVH grades I–II and III–IV were noted in 39.73% (240/604) and 1.66% (10/604) of the VPIs, respectively. Univariate analysis revealed that IVH occurrence in VPIs is influenced by perinatal factors, invasive respiratory therapy, high-proportion breast milk feeding, start feeding with breast milk, the cumulative amount of early parenteral nutrition, postnatal complications, physical growth, and other factors (P < 0.05). After adjustments for gestational age, birth weight, and possible influencing factors through binary logistic regression analysis, the results revealed that high-proportion breast milk feeding and and start feeding with breast milk were associated with a lower total incidence of IVH. Further stratification showed that high-proportion breast milk feeding was associated with a lower incidence of grade I–II IVH. Similarly, breast milk feeding >50% in the first week was associated with a decreased incidence of total IVH and grade I–II IVH,. Conclusion: High-proportion breast milk feeding and breast milk feeding more than 50% of total intake during the first week might be protective factors for IVH grade I–II in VPIs, which further verified the neuroprotective effect of breast milk. In clinical practice, the construction of breast milk banks should be strengthened, breast milk feeding should be encouraged in neonatal intensive care units, and efforts should be made to increase breast milk feeding rates to improve the outcomes of VPIs.